The Influence of the Effectiveness of Using Electric Shuttle Buses as Transportation within the Campus Environment - Abdul Azis; Mahesa Jihadul Akbar Haryadi; Wahid Munawar; Sriyono Sriyono (Global Education Journal, 2026)
The advancement of technology for electric vehicles has stimulated the adoption of eco-friendly transport systems across multiple fields, including universities. The rising mobility activities across campus regions frequently result in traffic jams, increased fuel usage, and environmental degradation. As a result, various academic institutions have started to introduce electric shuttle buses as a viable internal transport option to promote sustainable transportation. The purpose of this research was to evaluate how effective the use of electric shuttle buses is in enhancing transportation efficiency on campus. A quantitative methodology utilizing an associative approach was adopted. Information was gathered via surveys sent to 80 users of the electric shuttle bus service at Universitas Pendidikan Indonesia (UPI). The tools for research underwent validity and reliability assessments, while the analysis of data included tests for normality, simple linear regression, t-tests, F-tests, and the determination of the coefficient (R²) using IBM SPSS software. The findings revealed that all items in the questionnaire were both valid and reliable, with Cronbach’s Alpha scores of 0.890 for Variable X and 0.830 for Variable Y. Regression analysis showed a positive connection between the use of electric shuttle buses and the effectiveness of transportation, with an R Square figure of 0.124, indicating that the usage of electric shuttle buses accounted for 12.4% of the transportation effectiveness on the campus. The results of the F-test indicated that the regression framework was statistically significant, while the t-test showed that the independent variable did not have a considerable individual impact. In summary, electric shuttle buses can effectively aid in developing eco-friendly and sustainable transportation systems on campuses.